2012
DOI: 10.1016/j.pmrj.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Exercise During Pregnancy

Abstract: There is a direct link between healthy mothers and healthy infants. Exercise and appropriate nutrition are important contributors to maternal physical and psychological health. The benefits and potential risks of exercise during pregnancy have gained even more attention, with a number of studies having been published after the 2002 American College of Obstetrics and Gynecologists guidelines. A review of the literature was conducted by using PubMed, Scopus, and Embase to assess the literature regarding the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 85 publications
6
58
0
8
Order By: Relevance
“…Given past research indicating that exercise is positively associated with body satisfaction during pregnancy (Boscaglia et al, 2003;Goodwin et al, 2000;Prather et al, 2012;Symons Downs et al, 2008), it is somewhat surprising that physical activity habit strength did not protect women against declines in body satisfaction. This may be because the current sample exhibited a restricted range of physical activity habit strength, which may have decreased the chances of detecting an association between physical activity habit strength and body satisfaction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given past research indicating that exercise is positively associated with body satisfaction during pregnancy (Boscaglia et al, 2003;Goodwin et al, 2000;Prather et al, 2012;Symons Downs et al, 2008), it is somewhat surprising that physical activity habit strength did not protect women against declines in body satisfaction. This may be because the current sample exhibited a restricted range of physical activity habit strength, which may have decreased the chances of detecting an association between physical activity habit strength and body satisfaction.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies indicate that regular exercise and positive dietary behaviours are related to body satisfaction in pregnant women (Boscaglia, Skouteris, & Wertheim, 2003;Crow, Agras, Crosby, Halmi & Mitchell, 2008;Goodwin, Astbury, & McKeeken, 2000;Prather, Spitznagle, & Hunt, 2012). Repetition of health behaviours is particularly important, as it forms the basis of habits, which can be defined as "learned sequences of acts that have become automatic" (Verplanken & Aarts, 1999, p. 104).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise during pregnancy is safe for the mother, fetus, and child [25][26][27][28]. Maternal exercise during pregnancy can improve cardiovascular function in women during pregnancy without adverse effects on fetal growth [27][28][29]. For example, research has shown that pregnant women who exercise have a lower HR at rest and during exercise, increased stroke volume, and increased oxygen uptake [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of leisure physical activity for maternal [1][2][3][4] and fetal [5][6][7][8] outcomes are well documented in the literature. However, the level of leisure physical activities in pregnancy is low 5,7,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%